Cryptanura sp. (HYMENOPTERA: ICHNEUMONIDAE: CRYPTINAE), PARASITOIDS OF Taeniotes scalatus GMELIN (COLEOPTERA: CERAMBYCIDAE: LAMINAE) IN PANAMÁ (Aporte Santiaguino, 2021)
The wasps in the family Ichneumonidae are parasites of other insects, like Coleoptera, Diptera, Neuroptera and Lepidoptera, and are present in all land biomasses. Cryptinae is the largest subfamily and includes some of the most named species, very important in the biocontrol of other species that occasionally damage cultivated wood and the control of dangerous insects that attack trees. Two larvae of Taeniotes scalatus Gmelin (Coleoptera. Cerambycidae: Laminae) were collected that showed signs being parasitized by a Cryptanura sp wasp (Hymenoptera: Ichneumonidae: Cryptinae). In a fallen tree, Lacmella panamensis (Apocynaceae) we found larva of Taeniotes scalatus Gmelin that was parasitized by a Cryptanura sp wasp. Biological and ecological data of the parasitoid and the host are mentioned in this work.